All-American TV crime drama: feminism and identity politics in Law & Order: Special Victims Unit - Moorti, Sujata and Cuklanz, Lisa M. (Library of gender and popular culture, 2016)
"Law & Order: Special Victims Unit (SVU) is more popular than any other American police procedural television series, but how does its unique focus on sex crimes reflect contemporary popular culture and feminist critique, whilst also recasting the classic crime narrative? All-American TV Crime Drama is the first dedicated study of SVU and its treatment of sexual violence, gender and criminality. This book uses detailed textual and visual analyses of episodes to illuminate the assumptions underpinning the program. Although SVU engages with issues pertaining to feminism and gender, it sill relies upon traditional and misogynistic tropes such as false rape charges and the monstrous mother to undermine positive views of the feminine. The show and its backdrop, New York City, thus become a stage on which national concerns about women, gender roles, the family and race are carried out. Moorti and Cuklanz unpack how the show has become a crucible for examining current attitudes towards these issues and include an analysis of its reception by its many fans in over 30 countries"--Publisher's description
https://katalog.adlr.link/Record/0-1748110160